2017
DOI: 10.5194/hess-2017-93
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Three novel copula-based bias correction methods for daily ECMWF air temperature data

Abstract: Abstract. Data retrieved from global weather forecast systems are typically biased with respect to measurements at local weather stations. This paper presents three copula-based methods for bias correction of daily air temperature data derived from the European Centre for Medium-range Weather Forecasts (ECMWF). The aim is to predict conditional copula quantiles at different unvisited locations, assuming spatial stationarity of the underlying random field. The three new methods are: bivariate copula quantile ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The average bias for all stations equals 3.9 • C and 3.4 • C at d 6 and d 22 , respectively. We applied a bias correction method to obtain bias corrected values (Alidoost and Stein, 2016). A two-sample Kolmogorov-Smirnov test was performed of the null hypothesis that measurements and bias corrected values are drawn from the same distribution.…”
Section: Applicationmentioning
confidence: 99%
“…The average bias for all stations equals 3.9 • C and 3.4 • C at d 6 and d 22 , respectively. We applied a bias correction method to obtain bias corrected values (Alidoost and Stein, 2016). A two-sample Kolmogorov-Smirnov test was performed of the null hypothesis that measurements and bias corrected values are drawn from the same distribution.…”
Section: Applicationmentioning
confidence: 99%
“…Piani and Haerter (2012) used empirical copulas to bias correct temperature and precipitation simultaneously and concluded that after the correction, the relationship between the two variables was unchanged. Copulas were also used in a few studies considering bias correction of temperature and precipitation data, each variable was corrected separately but at different locations (e.g., Alidoost et al ., 2017; Lazoglou and Anagnostopoulou, 2019). In addition to bias correction, copulas in climatology are used to investigate trends in extreme precipitation and temperature, as in Mirakbari et al .…”
Section: Introductionmentioning
confidence: 99%
“…Copulas were also used in a few studies considering bias correction of temperature and precipitation data, each variable was corrected separately but at different locations (e.g., Alidoost et al, 2017;Lazoglou and Anagnostopoulou, 2019). In addition to bias correction, copulas in climatology are used to investigate trends in extreme precipitation and temperature, as in Mirakbari et al (2020).…”
Section: Introductionmentioning
confidence: 99%
“…At present, the forecast centers in various countries and regions provide many products of model forecast. Among them, the European Centre for Medium-Range Weather Forecasts (ECMWF) model forecast products have become widely used by various regional operational forecast centers in China, including temperature [28][29][30][31] and precipitation [23,32,33], even tropical cyclone path and intensity forecasts and other products [34]. At the same time, some evaluation studies on regional forecasts in China show that the forecast accuracy of ECMWF model is higher than those of the other forecast centers.…”
Section: Introductionmentioning
confidence: 99%